Mobility, Agency, Kinship
XV, 272 p. 4 illus., 3 illus. in color.
Keywords: This volume offers new perspectives on the ways in which migrants use storytelling practices and kinship formations in order to navigate and modify spaces of sovereignty, and thus to re-write narratives portraying them as helpless and passive victims. It provides one of the first investigations that assembles multidisciplinary contributions to look beyond individual acts of migrant agency and toward the entanglements of individual and collective agency, formations of kinship structures, and feelings, expressions, and representations of community and (multiple) belonging(s). The contributions explore the interplay between agency, kinship, and migration from various fields, including sociology, psychology, philosophy, border studies, gender and queer studies, postcolonial studies, ecocriticism, film and media studies, and literary and cultural studies – with a special focus on interdisciplinary narrative theory. They address real and imagined assertions of migrant agency and kinship formations; draw on empirical research, interviews, and accounts of lived experiences; and analyze the role of narrative, media, and technologies in artistic, literary, and cinematic representations of migrant agency and kinship. Lea Espinoza Garrido is a researcher and lecturer in the field of American Studies at the University of Wuppertal, Germany, where she is also co-chair of the “Narrative Research Group” of the Center for Narrative Research. Carolin Gebauer is a postdoctoral researcher and lecturer in British Literature and Culture at the University of Wuppertal, Germany, and a board member of Wuppertal’s Center for Narrative Research. Julia Wewior is a researcher and lecturer in the field of American Studies at the University of Wuppertal, Germany, where she is a board member of the Center for Narrative Research.